Impaired response to treatment with tumour necrosis factor α inhibitors in smokers with axial spondyloarthritis. Issue 3 (9th February 2015) - Ciurea, Adrian; Scherer, Almut; Weber, Ulrich; Exer, Pascale; Bernhard, Jürg; Tamborrini, Giorgio; Riek, Myriam; Müller, Rüdiger B; Weiss, Bettina; Nissen, Michael J; Kissling, Rudolf; Michel, Beat A; et al.
Abstract : Objectives: To investigate the impact of smoking on the response to treatment with a first tumour necrosis factor inhibitor (TNFi) in patients with axial spondyloarthritis (axSpA) in a real-life cohort. Methods: Patients fulfilling the Assessment of SpondyloArthritis international Society (ASAS) classification criteria for axSpA in the Swiss Clinical Quality Management Cohort were included in this study. The potential association between smoking status and differential response to TNFi in terms of the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and the Ankylosing Spondylitis Disease Activity Score (ASDAS) was analysed using multiple adjusted longitudinal mixed effect models. Binary response rates at 1 year were assessed with multiple adjusted logistic analyses. Results: A first TNFi was initiated in 698 patients with axSpA with available smoking status and a baseline or follow-up BASDAI assessment, of which 490 (70%) had complete covariate data. In comparison to non-smokers, current smokers demonstrated significantly smaller reductions in BASDAI and ASDAS scores upon treatment with TNFi (0.75 BASDAI units and 0.69 ASDAS units less, p=0.005 and 0.001, respectively) for patients with elevated baseline C-reactive protein (CRP) level. This effect was numerically smaller in patients with normal CRP. The odds for reaching a 50% improvement in BASDAI response or the ASAS criteria for 40% improvement after 1 year were significantly lower in current smokers than in non-smokers (0.54, 95% CI 0.31 to 0.95, p=0.03 and 0.43, 95% CI 0.24 to 0.76, p=0.004, respectively). Conclusions: Current smoking is associated with an impaired response to TNFi in axSpA.